Effectiveness of cadaver‐based educational seminar for trauma surgery: skills retention after half‐year follow‐up. Issue 1 (19th July 2016) - Homma, Hiroshi; Oda, Jun; Yukioka, Tetsuo; Hayashi, Shogo; Suzuki, Tomoya; Kawai, Kentaro; Nagata, Katsuhiro; Sano, Hidefumi; Takyu, Hiroshi; Sato, Norio; Taguchi, Hirokazu; Mashiko, Kazuki; et al.
Abstract : Aim: In Japan, trauma surgery training remains insufficient, and on‐the‐job training has become increasingly difficult because of the decreasing number of severe trauma patients and the development of non‐operative management. Therefore, we assessed whether a 1‐day cadaver‐based seminar is effective for trauma surgery training. Methods: Data were collected from 11 seminars carried out from January 2013 to March 2014, including a 10‐point self‐assessment of confidence levels (SACL) for 21 surgical skills and an evaluation of the contents before, just after, and a half‐year after the seminar. Statistical analysis was undertaken using the paired t ‐test at P < 0.0167. Results: A total of 135 participants were divided into three groups based on experience and clinical careers. The SACL improved in all skills between before and just after the seminar, however, they decreased between just after and a half‐year after the seminar. The SACL did not change significantly in all skills between just after and a half‐year after the seminar in highly experienced and experienced group members belonging to an emergency center. Conclusions: A cadaver‐based seminar provided more self‐confidence just after the seminar for participants at all experience levels. This effect was not maintained after a half‐year, except in participants who can practice the skills at an emergency center. Practicing and participating in the seminar repeatedly is suggested to be effective for skills retention in trauma surgery.